A numerical, theoretical and experimental study of the effect of thermocycling on the matrix-filler interface of dental restorative materials. Issue 5 (May 2021) - Boussès, Yoan; Brulat-Bouchard, Nathalie; Bouchard, Pierre-Olivier; Tillier, Yannick
Highlights: Dental composite yield stress is damaged by thermal cycles in "hot" and "cold" water. Turcsányi model indicated that the filler-matrix interface is protected in the first stage of ageing. The damage of this interface is responsible for the sudden decrease of mechanical properties in a second phase. Thermal stress is concentrated close to the filler-matrix interface. SEM pictures of debonded particles and profilometry measurements showed the weakness of the interface. Abstract: Objective: Thermocycling is widely used to age dental composites but with very different results from one study to another, even with apparent similar conditions. This study aims at understanding better the relative damaging speed of matrix and fillers, based on theoretical models. Methods: Eight formulations of an experimental dental material were produced. The same organic matrix was used and silanated barium glass particles were added as fillers with different filler ratios. Samples were thermocycled up to 10 000 cycles. Three-point bending tests were carried out at different steps. The yield stress was measured among other mechanical properties. Results: Composite properties were degraded by thermocycling. The decrease was slight during the first 5 000 cycles whereas it decreased significantly after 10 000 cycles. The Turcsányi model asserts that the interface yield stress is slightly affected in the first 5 000 cycles and then falls down, while the decrease of matrix yield stress is linear. Significance: Each component of a composite does not age at the same rate. First, the matrix acts as a protector until the water finds its way to the interphase. The filler silanization treatment is highly sensitive to hydrolysis and is damaged rapidly from that moment. Numerical simulations and surface observations confirmed that cracks appear to propagate in the neighbourhood of the interface but not directly within it.